Transparent-grid scheme for generating cathode-emittance-dominated beams in a gridded thermionic gun - Asaka, Takao; Nishimori, Nobuyuki; Inagaki, Takahiro; Otake, Yuji; Tanaka, Hitoshi (Japanese Journal of Applied Physics, 2021)
A transparent-grid scheme is proposed for generating cathode-emittance-dominated beams in a gridded thermionic gun. In the proposed scheme, the grid emittance arising from the potential difference between the grid and grid-mesh center is suppressed by tuning the grid voltage to the gridless gun potential. We developed a 50 kV gridded thermionic gun that is followed by a 238 MHz cavity for 500 kV acceleration. The measured projected emittance as a function of grid voltage shows a clear minimum approaching the cathode emittance and agrees well with a numerical simulation and a theoretical grid emittance taking into account the longitudinal space-charge effect. The measured minimum emittance for a core part which represents 60% of a 1-nC electron bunch is 1.5 m rad making the transparent-gridded thermionic gun a promising electron source for high brightness beam application such as a soft X-ray free-electron laser.